Apreciación del empleador sobre el impacto laboral obtenido por egresados del programa de Psicología de la Universidad de la Costa – CUC (2015)
This research integrates the main theoretical and empirical referents derivatives of the situational analysis of current graduates of the Program of Psychology from the Universidad de la Costa and its impact in the applied context. The methodological approach was descriptive transactional and counted with the participation of 30 employers. The results illustrate the appreciation that employers make regarding the performance, achievements and skills that manifest graduates in the workplace. The recognition of the quality and performance of graduates stands. Additionally it is positioning there in the middle of the relevance of the programs offered by the institution highlighted These findings allowed the statements were made of a series of strategic recommendations aimed at strengthening and continuous improvement of the follow-up and impact of the graduates in the middle, consolidating its disclosure with the development of research and extension projects.